Tingkat Keseriusan Pelanggaran, Efek Pengamat, dan Niat Whistleblowing - Fadillah, Ashya; Misra, Fauzan (E-Jurnal Akuntansi; Vol 34 No 2 (2024)DO - 10.24843/EJA.2024.v34.i02.p14, 2024)
Currently, fraud remains a significant issue within organizations. Therefore, it is necessary to implement whistleblowing policies as one of the preventive measures. This research aims to analyze the influence between the seriousness of violations and the bystander effect on whistleblowing intentions, as well as to examine the influence of the seriousness of violations on the bystander effect on whistleblowing intentions. This study employs a 2x2 factorial between-subjects design involving 118 participants from undergraduate accounting students at the Faculty of Economics and Business, Universitas Andalas. The results indicate differences in whistleblowing intentions between high and low seriousness violation levels, as well as between conditions with and without the bystander effect. The seriousness of violations can increase whistleblowing intentions, while the bystander effect can decrease whistleblowing intentions. Furthermore, this study successfully demonstrates that the seriousness of violations can moderate the influence of the bystander effect on whistleblowing intentions.The results of this study are expected to enrich the literature for the development of science and also as a consideration for organization on whistleblowing policies. Keywords:Seriousness Of Violations; Bystander Effect; WhistleblowingIntention